2012
DOI: 10.1038/jcbfm.2012.103
|View full text |Cite
|
Sign up to set email alerts
|

Painted Turtle Cortex is Resistant to anin VitroMimic of the Ischemic Mammalian Penumbra

Abstract: Anoxia or ischemia causes hyperexcitability and cell death in mammalian neurons. Conversely, in painted turtle brain anoxia increases c-amino butyric acid (GABA)ergic suppression of spontaneous electrical activity, and cell death is prevented. To examine ischemia tolerance in turtle neurons, we treated cortical sheets with an in vitro mimic of the penumbral region of strokeafflicted mammalian brain (ischemic solution, IS). We found that during IS perfusion, neuronal membrane potential (V m ) and the GABA A rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 44 publications
(76 reference statements)
2
14
0
Order By: Relevance
“…As a result, the brain of this species is remarkably tolerant of complete anoxia and also of global or focal ischaemia and high K + insults (Pamenter et al . ). To reduce cellular energy consumption during anoxia, AP firing frequency decreases due to a neuroprotective strategy termed spike arrest (SA) (Perez‐Pinzon et al .…”
Section: Introductionmentioning
confidence: 97%
“…As a result, the brain of this species is remarkably tolerant of complete anoxia and also of global or focal ischaemia and high K + insults (Pamenter et al . ). To reduce cellular energy consumption during anoxia, AP firing frequency decreases due to a neuroprotective strategy termed spike arrest (SA) (Perez‐Pinzon et al .…”
Section: Introductionmentioning
confidence: 97%
“…Elegant studies from a number of groups, particularly those of Frank Sharp [40], Jeffrey Gidday [12], John Zhang [54, 55], Gabriel Haddad [29], Sylvain Dore [52], and Mary Stenzel-Poore and Roger Simon [44], have shown that the ischemic-tolerant brain is characterized by both repression and activation of gene expression. These studies have been complemented by an understanding of the “proteomic signature” that is associated with such induction and repression [43].…”
Section: Introductionmentioning
confidence: 99%
“…It is understood that PKCε plays an important role in IPC in mammalian neurons, as demonstrated by its membrane translocation during IPC and its importance in limiting infarct damage during ischemia and reperfusion (Kawamura et al, 1998). One could make the argument that the western painted turtle and other anoxia-tolerant organisms are chronically pre-conditioned for periods of anoxia and ischemia, as these organisms can tolerate ischemic episodes without shorter, sub-lethal preceding exposures (Pamenter et al, 2012). By this argument, it would be logical to presume that factors critical for IPC in anoxia-sensitive organisms would be highly expressed at rest in anoxia-tolerant organisms.…”
Section: A Potential Role For Pkcε In Anoxia-tolerant Turtle Neuronsmentioning
confidence: 99%